Prognostic value of ambulatory blood pressure in chronic kidney disease - Kumar, S. Senthil; Vithiavathi, S.; Parameswaran, P. (International Journal of Advances in Medicine, 2018)
Background: Hypertension control is essential to prevent macro vascular complications in patients with chronic kidney disease. Ambulatory Blood Pressure Monitoring (ABPM) is the recognized gold standard for the assessment of hypertension and hence in this study ABPM assessment was done in 50 patients with dialysis dependant CKD to evaluate the adequacy of BP control and prevent adverse events. Methods: This study is a prospective observational study conducted at Aarupadai Veedu Medical College and Hospital, Pondicherry among hypertensive patients with dialysis dependant CKD patients as per standard criteria. A total of 50 patients participated in this study of both gender after obtaining written consent. Patients with coronary artery disease, diabetes mellitus, acute kidney injury were excluded from this study. Results: Out of the total 50 patients included in this study 72% had early morning dipping in BP and remaining 28% had non-dipping in systolic and diastolic pressure. The mean systolic pressure reached a maximum of 160.95mmHg to a minimum of 113.38mmHg and the mean diastolic pressure with a maximum of 98.47 to a minimum of 62.71mmHg on an overall 24 hours ABPM monitoring. The mean systolic and diastolic pressure was found to be more in the active period than in the passive period. Conclusions: Nocturnal BP is superior to day time BP in predicting CVD outcomes. This study shows both systolic and diastolic pressure variability over 24hrs maximum during night hours (nocturnal hypertension) and non-dipping of early morning BP. Both non-dipping status and nocturnal hypertension are associated with target organ damage and CV risk.